Moth-eye Structured Polydimethylsiloxane Films for High-Efficiency Perovskite Solar Cells - Kim, Min‑cheol; Jang, Segeun; Choi, Jiwoo; Kang, Seong Min; Choi, Mansoo (Nano-Micro Letters, 2019)
Large-area polydimethylsiloxane (PDMS) films with variably sized moth-eye structures were fabricated to improve the efficiency of perovskite solar cells. An approach that incorporated photolithography, bilayer PDMS deposition and replication was used in the fabrication process. By simply attaching the moth-eye PDMS films to the transparent substrates of perovskite solar cells, the optical properties of the devices could be tuned by changing the size of the moth-eye structures. The device with 300-nm moth-eye PDMS films greatly enhanced power conversion efficiency of 21% due to the antireflective effect of the moth-eye structure. Furthermore, beautiful coloration was observed on the 1000-nm moth-eye PDMS films through optical interference caused by the diffraction grating effect. Our results imply that moth-eye PDMS films can greatly enhance the efficiency of perovskite solar cells and building-integrated photovoltaics. Highlights: 1 Moth-eye structured polydimethylsiloxane (PDMS) films with different sizes were fabricated to improve the efficiency of perovskite solar cells. 2 The PDMS with 300-nm moth-eye films significantly reduced light reflection at the front of the glass and therefore enhanced the solar cell efficiency of 21%. 3 The PDMS with 1000-nm moth-eye films exhibited beautiful coloration. <figure> <picture><source srcset="//media.springernature.com/lw685/springer-static/image/art%3A10.1007%2Fs40820-019-0284-y/MediaObjects/40820_2019_284_Figa_HTML.jpg?as=webp" type="image/webp"></picture> </figure>